INTERNALISASI NILAI-NILAI KARAKTER KEWIRAUSAHAAN DALAM PEMBELAJARAN KETERAMPILAN TATA BOGA DI SLB: Studi Fenomenologis pada SMALB Tunarungu di SLBN Cicendo Bandung, SLBN Citeureup Cimahi dan SLBN 2 PKPLK Cimahi - Aep Saefulah, - (2023)
The lack of absorption of deaf people in the world of work and entrepreneurship is a problem for the world of education, especially regarding the hope of achieving independence and welfare. One of the opportunities for deaf people is entrepreneurship. The field of entrepreneurship that is possible is culinary because almost all schools develop lessons in culinary skills. In addition, it is a basic human need and does not always require large capital and can be run like a home business. But in reality, deaf people are still rare and very few become entrepreneurs. The problem is that in addition to the constraints of communication barriers in deaf people, the other is that the teacher who guides culinary skills is not optimal in carrying out the process of internalizing entrepreneurial character values as the basis of character that deaf students must have. The results of the study showed that, 1) entrepreneurial character values are developed in planning the implementation of learning that refers to the curriculum of educational units that have been determined by the school, 2) the implementation of culinary skills learning carried out applies entrepreneurial character values that are integrated in the learning process by applying models and media and approaches that are in accordance with the characteristics of deaf students, 3) evaluation in internalizing character values Using the provisions in the curriculum used, 4) Constraints on the implementation of internalization of entrepreneurial character values are based on understanding language concepts, especially in interpreting character values which for deaf students are still abstract. Keywords: character value, deafness, entrepreneurship, internalization,